On the macroscopic modelling of elastic/viscoplastic composites - Woźniak, Cz.; Wierzbicki, E. (Archives of Mechanics, 2002)
The aim of this contribution is to formulate a macroscopic model for the analysis of dynamic problems in micro-periodic composites made of elastic/viscoplastic and/or linear viscoelastic materials. The proposed modelling approach is based on the concept of tolerance averaging which so far was applied to the linear elastodynamics and heat transfer in periodic materials and structures. The obtained model equations, in contrast to homogenized equations, describe the effect of microstructure size on the overall behaviour of a composite solid.